What is the answer for question 3) ?

http://postimg.org/image/5keqi162t/

### 1 Answer | Add Yours

Take note that f(x) = y.

So, we can write the function as:y = 3x - 7.

To take the inverse function, we will swap the x and y, and then solve for y.

`x = 3y - 7`

Isolate the term with "y" on one side. We can do this by adding 7 on both sides.

`x + 7 = 3y`

Divide both sides by 3.

`y = (x + 7)/3`

Therefore the **final answer is: f ^-1(x) = (x + 7)/3**.

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes